SIRT1 activators as novel therapy for cancer - Marwah Saad Joudah; Basma Talib Al-Sudani; Inam Sameh Arif (College of Pharmacy / Mustansiriyah University, 2019)
Sirutins 1-7 (SIRT1-7) is an enzyme that depends on NAD+ to be activated, making it a member of the 3rd class of Deacetylase enzymes. SIRT1-7's activity is involved with metabolism, cell survival and/or death as well as DNA repair, gene repression, inflammatory responses, the   aging process, neuroprotection in addition to possibly helping with the treatment of cancer. Molecules that could have a modifying effect on SIRT1-7's activity has caught a great attention recently, owing to the fact of how beneficial this enzyme could be. In this review, we attempt to shed a light on these activator compounds and their use in Sirutin activation therapy, particularly SIRT1, for it is the most researched type. One of these compounds is Resveratrol, a natural compound that -due to its SIRT 1 activation potential - could help in the treatment of obesity, prevention of tumor formation as well as decrease in heart function and neuronal loss related to aging; however, Resveratrol has poor bioavailability, which is why structurally reformulated compounds and molecules have been developed. Other molecules that are different from Resveratrol such as SRT1720, SRT2104 and SRT2379 in addition to others, have been used and shown greater activation potential for SIRT1 than Resveratrol.